2012
DOI: 10.1148/radiol.12110066
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Anterior-to-Posterior Lesions: Comparison of External Rotation and Active Supination CT Arthrography with Neutral CT Arthrography

Abstract: ERAS CT arthrography might improve the detection of SLAP lesions compared with neutral-position CT arthrography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, the diagnosis of labral tears remains challenging due to subtle imaging findings, anatomical variations and pitfalls (14). This is why many different stress positions have been evaluated in shoulder MR arthrography over the past 15 years (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the diagnosis of labral tears remains challenging due to subtle imaging findings, anatomical variations and pitfalls (14). This is why many different stress positions have been evaluated in shoulder MR arthrography over the past 15 years (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the superior labrum, Jung et al found that the addition of external rotation to shoulder MR arthrography was helpful in the diagnosis of SLAP lesions and provided additional information about the displaceability of the torn labrum (17). Moreover, Choi et al recently reported that external rotation of the shoulder with active supination of the wrist improved the detection of SLAP lesions, compared with CT arthrography in neutral position (18). Joint distraction with axial traction might be complementary to such stress positions.…”
Section: Discussionmentioning
confidence: 99%
“…External rotation and active supination CT arthrography has been introduced in the diagnosis of SLAP lesions by Choi et al [2] who reported that this method showed superior diagnostic performance to the conventional neutral CT arthrography. The external rotation and active supination maneuver, using a positioning device, places the long head of the biceps under tension by external rotation of the humerus (passive tension) and active supination of the forearm (active tension).…”
Section: Introductionmentioning
confidence: 99%
“…The external rotation and active supination maneuver, using a positioning device, places the long head of the biceps under tension by external rotation of the humerus (passive tension) and active supination of the forearm (active tension). This tension drags the superior labrum from the glenoid; this positioning allows for the potential evaluation of the stability of the labrum at the glenoid [2]. It is regarded as unstable if the gap between the labrum and glenoid widens in external rotation and active supination position CT arthrography compared with neutral position CT arthrography.…”
Section: Introductionmentioning
confidence: 99%
“…CT arthrography is an alternative method used to diagnose shoulder abnormalities-in particular, labral lesions [3][4][5]. Direct MR and CT arthrography are somewhat invasive procedures, however, and patients often complain afterward of arthrography-related pain [6][7][8][9].…”
mentioning
confidence: 99%